Contribuições à genética e melhoramento de alfaces mediante cruzamentos e cultura de tecidos - Santos, Aparecida Célia Paula dos (1996)
Lettuce (Lactuca sativa) is among the most consumed vegetables by Brazilians and is widely cultivated. Unfavorable environmental factors and diseases affect their cultivation. Most cultivars for sale on the market are low in p-carotene. The cultivation of lettuce cultivars rich in vitamin A with sweeter taste, tolerance to septoriosis, broadleaf, tolerance to heavy summer rains, late inflorescence, adapted to pH 4 to 8, was the object of this work. The cultivars Moreninha de Uberlândia, Maioba, Vitória de Santo Antão and Simpson were used. Two methodologies were employed: Ia) culture of the cotyledon proximal portion in modified MS medium. 2a) crosses between four cultivars, self-fertilization and selection for the characters of interest. The methodology for determination of P-carotene was that of RODRIGUEZ et al. (1976). At 15 days after planting in modified MS medium, the cotyledons had corns, which were divided. After 13 days of this division they were fit for full MS regeneration medium. In 30 days the seedlings could be acclimatized and in 10 days they could be transferred to the field. Differences between the Po, Fb and F2 plants indicate that the regenerated lettuce of cotyledon crop develops somaclonal variation, which is capable of secreting heterozygous gene mutations. All 61 crossings made between Lactuca indica and Lactuca sativa did not form hybrids. Data from segregating population analysis suggest a relatively simple genetic determination for the traits: Resistance to the tipbum / susceptible, which is determined by the presence of 2 genes and modifiers; Single / forked head, 63: 1; Late / early spike, 15: 1; Septoriosis resistant / susceptible to 2 genes and modifiers; Lettuce / Coconut format, 63: 1; Wide / narrow sheet, 3: 1; Presence of anthocyanin / absence, 3: 1; Not bitter / bitter taste 13: 3 and Curly / smooth leaf 15: 1. Plants with anthocyanin were more resistant to septoriosis and tipbum. Tests on the plants affected by the tipbum were negative for the lettuce mosaic virus, so the cause of the disease remains unknown.